WATER CLEANING MODELING IN A HORIZONTAL SETTLER - Kozachyna, V. A.; Shynkarenko, V. I.; Bondarenko, I. O.; Gabrinets, V. A.; Horiachkin, V. M. (Science and Transport Progress, 2019)
Purpose. Improving the efficiency of wastewater treatment plants in water supply and sanitation is an important technical task. To analyze the effectiveness of water treatment of a particular structure, at the design stage, you need to have special mathematical models. The work is aimed to develop a numerical model of the mass transfer process in a vertical settler to assess its performance. Methodology. The spread of the pollutant in the treatment plant (settler) is calculated on the basis of the distribution equation of the impurity, which expresses the law of mass conservation. The modeling equation takes into account the convective transfer of impurities and the transfer of impurities due to turbulent diffusion. The mathematical model takes into account the uneven flow velocity field in the building. To determine this uneven flow velocity field, a mathematical model of the flow of an ideal fluid is used. In this case, the vortex nature of the flow is taken into account. Findings. The solution of modeling equations is found numerically. For numerical integration of the modeling transport equation in the structure, difference splitting schemes were used. The basic mass transfer equation is preliminarily split into equations that take into account the movement of an impurity in a settling tank due to convection, and into equations that take into account the transfer of an impurity due to diffusion. For numerical integration of the modeling equations of the inviscid fluid flow, implicit difference splitting schemes are used. The numerical calculation is carried out on a rectangular difference grid. Originality. A feature of the developed mathematical model is the possibility of modeling the velocity field and the process of impurity transfer taking into account the geometric shape of the settlers and the possibility of using plates in them, which affect the flow hydrodynamics in the structure and, therefore, the efficiency of water treatment. Practical value. The calculation time for one version of the task based on the constructed mathematical models is a few seconds. The models can be used to obtain an expert assessment of the operation of treatment facilities designed. The results of a computational experiment in determining the efficiency of the settler with two plates are presented.